Los griegos y la doctrina esotérica de los elementos - Casas Ulate, Ronald (2009)
According to Empedocles, a Greek philosopher, scientist, healer and ser, who lived in Sicily in the fifth century B.C., all m atter consists of “rootclumps” or elements. Empedocles described these elements not only as physical manifestations, but also as spiritual essences. He as associated them with four gods and goddesses. Empedocles philosophy was influenced by Pythagoras and by the ancient greek mystery traditions. In the works and practices of the alchemists, neoplatonists and gnostics that further developed his theories, the elements are not only material and spiritual forces, but also facets of a human being. Their varying combinations result in different personality types. Carl Gustav Jung (1875 – 1961), one of the founders of modern psychology, studied mystical literature and alchemy and his conceptualization of the four basic components of personality is a derivation of Empedocles ancient theories about earth, water, air and fire.